Effect of Intercropping Beans with Maize and Botanical Extract on Fall Armyworm (Spodoptera frugiperda) Infestation - Clovis Bessong Tanyi; Raymond Ndip Nkongho; Justin Nambangia Okolle; Aaron Suh Tening; Christopher Ngosong (International Journal of Agronomy)
African farmers are currently grappling with potential control measures for the invasive fall armyworm (FAW) (Spodoptera frugiperda), which has recently emerged as an important economic pest that is ravaging maize fields across the continent. We evaluated the efficacy of the West African black pepper extract and beans intercropping systems as viable FAW control measures and the implication on maize yields. The experiment comprised five treatments (control-no input, dwarf beans intercrop, climbing beans intercrop, West African black pepper extract, and insecticide) with three replications each. FAW severity was assessed at three to seven weeks after planting (WAP), while maize infestation was assessed at seven WAP. FAW severity increased significantly (P<0.05) across WAP for the control and dwarf beans intercrop, with the highest at four and six WAP, respectively. FAW severity also differed (P<0.05) significantly across treatments at four to seven WAP, with the lowest recorded in the extract of West African black pepper (Piper guineense) and the highest in control treatments. Maize infestation ranged from 13 to 93%, with the lowest in the West African black pepper extract and synthetic insecticide, followed by both dwarf and climbing beans intercrops and then the control. The maize yield determined at physiological maturity ranged from 2.2 to 6.3 t ha−1 across treatments and differed significantly, with the highest in the West African black pepper extract and synthetic insecticide, followed by both the dwarf and climbing beans intercrops, as compared to the control. Overall, the West African black pepper extract and beans push cropping systems demonstrated efficacy as viable sustainable alternative control measures for the invasive fall armyworm in maize fields.